As Discussões De Vygotsky Sobre Defectologia: Necessidades Para A Formação De Professores Na Perspectiva Da Educação Inclusiva - Silva, Eliane Pereira Domingues Da [UNIFESP] (2018)
The Present Work Aims At Analyzing And Understanding How Vygotsky"S Concepts, Based On The Defectology Studies, Can Contribute To The Education Of Teachers, In Order To Establish An Inclusive Pedagogical Practice That Can Ensure The Access And The Permanence Of Students With Special Needs In Regular Schools. Teacher Education Is A Key Subject In The Context Of Inclusion (Ferreira, 2014), Provided That With The Knowledge About Students With Special Needs And The Theoretical And Practical Education On The Educational Performance, The Teacher Can Reframe The Pedagogical Practice To Meet The Needs Of Such Students (Pietro, 2006). Regarding The Contributions Of Vygotsky"S Socialhistorical-Cultural Theory To Education, We Emphasize The Studies In Defectology, Which Must Be Understood As The Science That, At Least In Vygotsky"S Conception, Is Based On The Premise That "The Child Whose Development Is Complicated By A Disability Is Not Simply Less Developed Than Its So Called `Normal" Peers, But Otherwise Develops In